Efektivitas Efektivitas Program CATCH Berbasis Tutor Sebaya Ditinjau dari Self-Efficacy dan Komunikasi Matematis Siswa - Setiana Setiana (Direktorat Guru Pendidikan Dasar, Kemendikbudristek R.I., 2021)
Self-efficacy and mathematics communication are problems associated with the CATCH program and are the subject of this research. The aim of this research is to know the effectiveness of CATCH program based on peer tutoring to self-efficacy and the students’ mathematics communication. CATCH program is develop into some levels, those are pre development, development, and post development. The Research and Development methodology that is used the system of Akker, it consists of introductionand formativetest with Tessemer as the guidance. It measures: self evaluation; expert review; one to one; small group; field test. The subject of this research is the students of Junior High School with 20 students of Grade 8. The self- efficacy scoring is got from self-efficacy scale and the data of mathematics communication ability based on mathematics communication test. The expert review shows that CATCH program based on peer tutoring to fulfill the standard of material, design, and language. The result of one to one test shows the positive result based on the students’ response after getting the program and the students’ responsibility towards the program. Then, the test of small group shows the positive result of the reading efficiency and their understanding. The research shows that the CATCH program based on peer tutoring is an effective way to improve self-efficacy and the students mathematics communication.